Six month old neglected metacarpophalangeal joint volar complex dislocation: a case study - Ambulgekar, Rajesh K.; Ghag, Niranjan S. (International Journal of Research in Orthopaedics, 2022)
Metacarpophalanegal dislocations are rare, accounting for 3-5% of all dislocations with thumb being the most common finger affected. these dislocations can be decided into volar and dorsal and further into simple and complex, depending upon direction of dislocation and reducibility respectively. Although there is no approach superior over another, we selected volar approach for better visualization and direct reduction of dislocation and found reduction was unstable. hence a temporary fixation was attempted with K-wire which was removed 7th day postoperative and started with physiotherapy. Postoperatively patient was having near total range of motion (25-90 degree) and patient was able to do all the routine daily activities with his affected hand post operative 2 month. Complex metacarpophangeal joint dislocations needs intervention and should be combined with vigorous postoperative physiotherapy to achieve good clinical outcomes.